COMMUNITY INVOLVEMENT AND SUSTAINABLE DEVELOPMENT IN MEGHALAYA’S NATURE-BASED TOURISM INDUSTRY - Kumar , Paramjeet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Situated in the northeastern area of India, Meghalaya entices both nature lovers and connoisseurs of culture with its abundant biodiversity and cultural legacy. This essay explores the complex relationship between community involvement and the admirable objective of sustainable development in the context of Meghalaya’s thriving ecotourism sector. Employing a multifaceted, interdisciplinary approach, we endeavor to decipher the intricate web of economic resilience, social inclusivity, and environmental integrity, all underpinned by the active participation of local communities. Drawing from a mosaic of empirical data harvested through comprehensive surveys, illuminating interviews, and incisive case studies, our pursuit is to furnish vital insights for the edification of policy architects, industry stakeholders, and the indomitable local communities, thus forging an indomitable path towards conscientious and sustainable tourism development in Meghalaya. As the emerald gem of India’s travel landscape, the responsible growth of Meghalaya’s nature-based tourism industry rests in the hands of those who call this pristine land home.